Railways in Development : Global Round-Up 1996-2005 - Amos, Paul (World Bank, Washington, DC, 2012)
This Transport Note has been prepared as an adjunct to the 2006-07 updating of the World Bank's Railways Databases (www.worldbank.org/railways). It uses the databases for inferences on aggregate trends (and so subject to the caveats provided in the Explanatory Note cited) as well as other Bank documents and sources of policy information. It provides a high level view of traffic and policy developments. Particular emphasis is given to the Bank's six regions of operations at a time when the Bank's Transport Strategy is being updated with the intention of increasing the attention given to the role of railways in development. For completeness, important policy developments in the higher income countries are also summarized.